Deux miracles de la sainte Vierge; Les 150 Ave du chevalier amoureux et Le sacristain noyé - Coincy, Gautier de; Rankka, E. (Uppsala Almqvist & Wiksells, 1955)
The Miracles of Our Lady by Gautier de Coinci, in 30,000 octosyllabic verses with flat rhymes, were written between 1218 and 1233; they are accounts of miracles with the same narrative scheme: the hero stands out for his veneration for the Virgin Mary; he succumbs to sin, but eventually repents and his devotion to Mary ensures his salvation. The poem was copied and illuminated in numerous manuscripts (48 are preserved today, in all 84 manuscripts have been identified).
The Miracles of Our Lady or miracles of the Blessed Virgin is a collection of dramatic miracle stories about the Virgin Mary written by Gautier de Coinci (1177-1236).
These stories, often inspired by Latin models, would in turn inspire a number of authors, including those of dramatic miracles, such as Rutebeuf's Le Miracle de Théophile, or those of Marian songs, such as the Cantigas de Santa Maria, attributed to Alfonso X the Wise (king of Castile and León in the thirteenth century).
Keywords: Virgin Mary -- Saint; Middle Ages (500-1400); Mystery play; New Testament; France